THE ACUPUNCTURE TREATMENT IN A PATIENT WITH URINARY TRACT INFECTION AT SEHAT KANIDEE CLINIC IN BOGOR CITY - Wiwi Kania Dewi; Amal Prihatono; Mayang Wulandari; Ikhwan Abdullah (STIKes Mandala Waluya Kendari, 2026)
Background: Background: Urinary tract infection (UTI) is a common infectious disease with a high risk of recurrence and potential complications if not properly managed. In addition to pharmacological treatment, safe complementary approaches may help support symptom improvement. Acupuncture is a complementary therapy that has been applied in various urinary system disorders. This study aimed to explore the benefits of acupuncture care for a patient with UTI at Klinik Sehat Kanidee, Bogor. Methods: A clinical case study design with a descriptive qualitative approach was used. The subject was one patient diagnosed with UTI. Acupuncture therapy was administered in six sessions, twice weekly. Diagnosis and evaluation were conducted using the four diagnostic methods of Traditional Chinese Medicine. Results: Outcome measures included changes in dysuria, urinary frequency, sensation of incomplete voiding, and overall patient condition. After six sessions, the patient showed gradual improvement in the main UTI symptoms. Dysuria and the sensation of incomplete voiding resolved, urinary frequency returned to normal, and the general condition improved. From an acupuncture perspective, improvement in Spleen and Kidney Qi deficiency syndrome was observed. Conclusion: Conclusion: Acupuncture may provide clinical benefits and can be considered a complementary therapy in UTI management.